Experimental study of slender concrete-filled elliptical hollow section beam-columns. (October 2015) - McCann, F.; Gardner, L.; Qiu, W.
Abstract: Experiments on concrete-filled elliptical hollow section beam-columns have been conducted to examine their fundamental structural behaviour. A total of 27 specimens were tested — 3 stub columns and 24 longer members of varying slenderness. Seven of the tested specimens also contained steel reinforcement. The specimens were loaded in compression, either concentrically or with different major or minor axis eccentricities. Measurements of the applied load, the strains at mid-height, the axial displacement and the lateral deflection at mid-height were recorded. Plots of load against the lateral deflection at mid-height and load against axial displacement are presented for the specimens, along with values of strength index and ductility index. Comparisons have been made between the test results and the provisions of the European Standard EN 1994-1-1:2004 for determining the ultimate load of concrete-filled circular and rectangular hollow section columns. It was found that the predicted resistances are safe for use in the design of concrete-filled elliptical hollow section columns either with or without reinforcement, and loaded either concentrically or eccentrically. Highlights: A number of concrete-filled steel elliptical hollow section columns and beam columns have been tested The member slenderness, presence of steel reinforcement, buckling axis and load eccentricity were varied across 27 specimens Deformation modes, ultimate loads, load–deflection behaviour, strength indices and ductility indices have been presented Comparison was made with Eurocode 4 provisions for CHS and RHS members; these provided safe predictions for ultimate load